Rigorous Tracking of Weld Beads for the Autonomous Inspection with a Climbing Robot - Terres, Vinicius; Oliveira, Andre; Santos, Higor; Arruda, Lucia; Neves, Flavio; Fabro, Joao; Ramos, Julio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This article presents a novel strategy for an autonomous inspection robot for oil industry tanks. The goal is to identify and track the external weld beads of a tank by an inspection robot. The chosen robot is an autonomous climbing robot with differential magnetic wheels. The detection of the weld bead is made with a line profile sensor. An algorithm is proposed to identify the weld bead position from the robot. The control is designed with the Fuzzy technique. The approach is evaluated on a real plate and a cylindrical tank virtually designed with the same characteristics that real tank projects.